Decision Support Systems in Cardiology: A Systematic Review; Studies in Health Technology and Informatics; Vol. 237 : Wearable, Micro and Nano Technologies for Personalised Health (pHealth 2017) - Dudchenko A. V. Aleksey Vitaljevich (2017, 2017)
Title screen